The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1017/s0952523800002595
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged depolarization in rods in situ

Abstract: Intracellular recordings were made from rods in the superfused retina of the marine toad (Bufo marinus). It was found that injection of a brief depolarizing current pulse (0.04-1 nA) evoked a distinctive, long-lasting response, here called "the prolonged depolarization." The response appears to be regenerative, has a stereotypical waveform, is typically about 6 mV in amplitude and 3 s in duration, and has a relatively long recovery period (10-60 s). As a rule, the response cannot be directly evoked by light bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Burkhardt et al (1988) showed evidence for three components in the surround responses of turtle cones: 1) an initial graded depolarization, 2) spikes, and 3) long regenerative events that lasted for many seconds and were termed “prolonged depolarizations.” Subsequent work showed that prolonged depolarizations are triggered by the regenerative activation of L-type Ca 2+ channels and exhibit a long-lasting plateau phase maintained by the activation of Ca 2+ -activated Cl − channels (Thoreson and Burkhardt, 1991; Barnes and Deschenes 1992). Prolonged depolarizing responses with similar waveforms have been observed in cones and rods from a number of species (turtle cones: Burkhardt et al, 1988; Cervetto and Piccolino, 1982; salamander cones: Lasansky, 1981; toad rods: Burkhardt et al, 1991; mouse rods: Babai and Thoreson, 2009). …”
Section: Negative Feedback From Horizontal Cells To Conessupporting
confidence: 56%
“…Burkhardt et al (1988) showed evidence for three components in the surround responses of turtle cones: 1) an initial graded depolarization, 2) spikes, and 3) long regenerative events that lasted for many seconds and were termed “prolonged depolarizations.” Subsequent work showed that prolonged depolarizations are triggered by the regenerative activation of L-type Ca 2+ channels and exhibit a long-lasting plateau phase maintained by the activation of Ca 2+ -activated Cl − channels (Thoreson and Burkhardt, 1991; Barnes and Deschenes 1992). Prolonged depolarizing responses with similar waveforms have been observed in cones and rods from a number of species (turtle cones: Burkhardt et al, 1988; Cervetto and Piccolino, 1982; salamander cones: Lasansky, 1981; toad rods: Burkhardt et al, 1991; mouse rods: Babai and Thoreson, 2009). …”
Section: Negative Feedback From Horizontal Cells To Conessupporting
confidence: 56%
“…Regenerative potentials have been recorded in rods during the recovery phase of the light response when the retina was treated with TEA to block potassium channels (Fain & Quandt, 1980; Fain et al 1980). A prolonged depolarization was also observed in rods after injection of brief depolarizing current pulses in cells with high internal chloride (Thoreson & Burkhardt, 1991; Burkhardt et al 1991). In 20% of cones in turtle retina, feedback from horizontal cells evokes a spike (Piccolino & Gerschenfeld, 1980).…”
Section: Resultsmentioning
confidence: 95%
“…In two rods, we observed large, prolonged depolarizing responses with waveforms similar to prolonged depolarizing responses found in rods and cones of other species (Burkhardt et al . 1988, 1991; Thoreson & Burkhardt, 1991; Barnes & Deschenes, 1992). These earlier studies showed that prolonged depolarizing responses begin when an initial small depolarization (e.g., due to activation of Ca 2+ -activated Cl − channels by CICR) stimulates the regenerative activation of voltage-gated Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 99%